Statistical Physics of Spin Glasses and Information Processing An Introduction - Nishimori, Hidetoshi (International Series of Monographs on Physics, 2001)
Spin glasses are magnetic materials with strong disorder. Statistical mechanics has been a powerful tool to theoretically analyse various unique properties of spin glasses. A number of new analytical techniques have been developed to establish a theory of spin glasses. Surprisingly, these techniques have offered new tools and viewpoints for the understanding of information processing problems, including neural networks, error-correcting codes, image restoration, and optimization problems. A vast, interdisciplinary field has consequently been developing between physics and information, or more specifically, between the statistical physics of spin glasses and several important aspects of information processing tasks. This book provides a broad overview of this new field. It also contains detailed descriptions of the theory of spin glasses.